Potential of the Betadine Plant (Jatropha multifida L) for Wound Healing: Literature Review - Nurhayati, Evalatifah; Ginting, Chrismis Novalinda; Nababan, Tiarnida (Jurnal Keperawatan Priority, 2024)
One of the therapies used in wound care is the betadine plant to accelerate wound healing. It contains active substances, including flavonoids, tannins, saponins, and alkaloids, which act as antioxidants, anti-inflammatories, and antimicrobials. The type of research carried out was a literature review type. Literature search regarding the potential of betadine plant leaf extract (Jatropha multifida L) for wound healing using Google Scholar, Pubmed, Sci-Hub, and Science Direct. Articles were selected based on exclusion and inclusion criteria, resulting in a sample of 7 articles in Indonesian and English. The research results show that using betadine plants can heal cuts, post-tooth extraction wounds, and chemical burns. Administration is carried out two times a day with a treatment time of 1 to 4 weeks, and evaluation is done twice during the intervention. Wound treatment uses the betadine plant as an alternative therapy, which is helpful for wound healing. It is hoped that the betadine plant can be used as an alternative in wound care and can be applied by the community, especially for DM sufferers.